Soil chemical properties in agroforestry and cassava cropping systems in Pati, Central Java - Ursulin Sacer Setyastika; Sri Rahayu Utami; Syahrul Kurniawan; Christanti Agustina (Brawijaya University, 2022)
Changes in natural land use for monoculture cropping systems may affect the soil properties over a certain period of time. In an attempt to evaluate soil chemical properties in the cassava cropping system, the research was conducted in Pati Regency, Central Java. Four land use systems were compared, i.e. monoculture cassava (cultivated for 5, 10, and 15 years) and agroforestry systems in two different slopes (i.e., 8-15% and 16-40%), with four replications. Soil samples from each location were taken at a depth of 0-20 and 21-40 cm for soil chemical analysis (pH, cation exchange capacity, organic C, total N, available P, exchangeable K, Ca, and Mg). Soils in agroforestry systems had higher pH, CEC, the content of organic C, total N, exchangeable K, Ca and Mg than in cassava cropping systems, especially on the slope of 8-15%. The soil under 15 years cassava and on the slope of 16-40% had the most degraded soil chemical properties, as reflected by the lowest content of organic C, total N, exchangeable K, and slightly lower CEC and the content of exchangeable Ca and Mg. Soil chemical properties on the slopes of 8-15% were significantly better than on the slopes of 16-40%, especially in CEC and the content of organic C, total N, exchangeable K and Mg. However, there was an unclear pattern of the available P content, which was possibly due to the application of P fertilizer in cassava cropping systems.